ProcCluster® and procaine hydrochloride inhibit the growth of Aspergillus species and exert antimicrobial properties during coinfection with influenza A viruses and A. fumigatus in vitro - König, Sarah; Schroeder, Josefine; Heinekamp, Thorsten; Brakhage, Axel A.; Löffler, Bettina; Engert, Beatrice; Ehrhardt, Christina (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionInfluenza-associated pulmonary aspergillosis is associated with high mortality rates and limited treatment options. The current standard practice involves treating each pathogen separately. However, the use of antifungal drugs can lead to serious side effects, and the presence of triazole-resistant Aspergillus strains can complicate antifungal therapy. In addition, drug-resistant influenza viruses are becoming an increasing concern in clinics. A drug that affects fungal and viral propagation could overcome these disadvantages. Thus, we conducted a study to examine the antifungal and antiviral properties of ProcCluster® and procaine hydrochloride (HCl), which are prodrugs derived from the local anesthetic procaine.MethodsConidia of different A. fumigatus strains, A. flavus and A. terreus were treated with the test substances in a human cell-free system and antifungal properties were analyzed either by fluorescence microscopy or absorption measurements. Changes in metabolic activity and intracellular Ca2+ distribution during treatment of A. fumigatus with ProcCluster® were observed using fluorescence microscopy. In addition, antifungal and antiviral properties of ProcCluster® and procaine HCl were investigated during in vitro coinfection of lung epithelial cells with A. fumigatus and influenza A viruses (IAV). Analysis was performed by fluorescence microscopy, standard plaque assay and Western blot assay.ResultsBoth substances inhibited the growth of the fungus, even when applied after germination or in the presence of purified IAV particles. ProcCluster® remained effective against triazole-resistant A. fumigatus strains. However, the addition of CaCl2 reversed the antifungal effect, indicating that ProcCluster® inhibited fungal growth by disrupting fungal Ca2+ homeostasis. Furthermore, in vitro studies showed that ProcCluster® and procaine HCl reduced the pathogen load of IAV and A. fumigatus during coinfection. Finally, the combination of ProcCluster® with the antiviral drug favipiravir exhibited increased antipathogenic activity, particularly against IAV replication.DiscussionThis research highlights ProcCluster® and procaine HCl as substances with anti-infective properties against various pathogens.